Prof Application of neuromuscular blockade using Rocuronium for performing different surgeries and its reversal by Neostigmine-Glycopyrrolate combination in dogs: - RANA, YUDHVIR; KUMAR, ADARSH; KUMAR, ROHIT; KUMAR, AMIT; TYAGI, S P; KAUSHAL, SARA; KUMAR, AKSHAY; SINGH, MANGAL; MAHANTESH, VIJAY; THAKUR, KALPNA (The Indian Journal of Animal Sciences, 2023)
This study was executed in the clinical setup to investigate the effects of Rocuronium and its reversal by Neostigmine and Glycopyrrolate (Myopyrolate) combination in Propofol-Isoflurane anaesthetized dogs. Rocuronium-induced neuromuscular blockade was applied to 21 clinical cases. Out of which, 19 cases were of orthopaedic surgeries and 2 cases of ovariohysterectomy. After the animal had stabilized on the mixture of isoflurane and oxygen, the relaxation of muscle was induced using Rocuronium @ 0.5 mg/kg b.wt. Immediately IPPV was provided in volume control mode. Neuromuscular blockade was reversed using a single syringe combination drug having both Neostigmine and Glycopyrrolate (Myopyrolate) @ 0.05 mg/kg b.wt and @ 0.01 mg/kg b.wt, respectively. Rocuronium caused the centering of the ocular globe gradually in less than 30 sec. During orthopaedic surgeries, the reduction of fractured ends became easy without much tissue trauma. In ovariohysterectomy surgeries, the appropriate level of abdominal muscle relaxation further helped in the easy exteriorization of the ovarian stump. The onset time for Rocuronium was 17.64±1.10 sec and its duration of action was 27.82±0.72 min. The use of Rocuronium along with IPPV caused minimal alteration of the physiological parameters with no clinical consequences and thus can be considered a complication-free anaesthetic protocol for interventions demanding muscle relaxation.